Implementasi Budaya 5R (Ringkas, Rapi, Resik, Rawat, Dan Rajin) Pada Kelompok Belajar Binaan Komplek Kodam Jatiwaringin - tirtana siregar; Bunga Kasih Asmarani; Cindy Alichia; Magdalena (LPPM Stikosa - AWS, 2021)
Application Of The 5R Culture (Sort, Stabilize, Shine, Standardize, Sustain) in the guided learning group RW 06 Komplek Kodam Jatiwaringin needs to be created and managed continuously so that this learning group can achieve success in the process and results so that every day the children will accustomed to neat culture. 5R Principle (Sort, Stabilize, Shine, Standardize, Sustain) is one of the working principles originating from Japan and has been widely used in large companies throughout the world. This study aims to identify providing counseling in the implementation or application of the 5S principle in every day activities in this association. This type of research is conducted by providing information about 5R in general terms that can be applied in everyday life and can even be a culture that must be maintained. Guided Study Group RW 06 The Jatiwaringin Regional Military Command complex numbered approximately 20-25 elementary level children to the first level. This counseling provides the results of implementing the 5R in the organization which will make this group in their childhood to adolescence able to regulate their life and daily activities regularly.